Senegal : Background Papers and Statistical Appendix. (IMF Staff Country Reports; Country Report, 1995)
This Background Paper and Statistical Appendix examines the factors that may have accounted for Senegal's growth, savings, and investment performance, focusing in particular on the response to adjustment policies since the mid-1980s. It provides an overview of the long-term economic performance in Senegal. The paper describes the initial conditions that led to an economic crisis in the late 1970s and early 1980s, and discusses the main obstacles to higher sustained growth. The paper also briefly examines the adjustment strategy implemented since the mid-1980s.